Brominated flame retardants in animal derived foods in the Netherlands between 2009 and 2014. (November 2019) - Gebbink, Wouter A.; van der Lee, Martijn K.; Peters, Ruud J.B.; Traag, Wim A.; Dam, Guillaume ten; Hoogenboom, Ron L.A.P.; van Leeuwen, Stefan P.J.
Abstract: Polybrominated diphenylethers (PBDEs), hexabromocyclododecanes (HBCDDs) and tetrabromobisphenol A (TBBPA) were monitored in various foods from terrestrial and aquatic animal origin (>850 samples), collected in the Netherlands between 2009 and 2014. The terrestrial samples included meat/fat from 7 animal species (including bovines, pigs, broilers and sheep), bovine milk and hen eggs. Dominant PBDE congeners in these samples were BDE-47, -99, -100, -153 and -183. The meat/fat generally contained the highest ∑PBDE concentrations compared to eggs and milk, with meat from deer, horse and sheep containing the highest concentrations. Generally declining ∑PBDE concentrations were observed between 2009 and 2014, however, this was only significant in pig meat and hen's eggs. The aquatic samples included fillets from 18 species (including herring, haddock and salmon), brown crab parts, shrimp and mussels, and the highest ∑PBDE concentrations were seen in body parts of brown crab, herring, mackerel, salmon and sea bass (on wet weight basis). Patterns generally contained more congeners (i.e., BDE-28, -49 and -66) additional to the aforementioned congeners found in terrestrial samples. Herring, sea bass and brown crab (body parts) contained among the highest PBDE concentrations. TBBPA was only detected in 3 individual samples (bovine and broiler meat and haddock), while α-HBCDD was the dominant diastereomer detected in several terrestrial and aquatic samples. When detected, TBBPA and HBCDD concentrations were generally in the same order as ∑PBDE concentrations in the same sample types. Graphical abstract: Image 1 Highlights: BFRs were detected in foods from 12 terrestrial and 21 aquatic species from the Netherlands. PBDEs were detected at a higher frequency compared to HBCDDs and TBBPA. BDE-47, -99, −100, −153 and −183 were commonly detected in all the samples. ∑PBDE concentrations declined significantly in meat from pigs and hen's eggs.